WHEAT SAMPLES AND HEAVY METALS - Miloš Rajković; Mirjana Stojanović; Đorđe Glamočlija; Dragan Tošković; Violeta Miletić; Violeta Stefanović; Časlav Lačnjevac (Journal of Engineering & Processing Management, 2012)
Plants have an important role in circuit of heavy metals in nature. Heavy metals are input into food chains mainly through plants. One of the ways in which heavy metals are input into food products is through contaminated plants and animals used for their production. So, if the plants are cultivated on soil with high content of heavy metals then one part of these metals will be input into their organism. The usage of such plants for domestic animals nourishment will lead to their contamination with heavy metals. Meat, milk and eggs of these animals will be of poor quality considering the high level of heavy metals in them. The other, not less significant way of contamination of food products with heavy metals is the technological process in which they have been made. Namely, due to some irregularities in technological processes it can come to input of certain metals in amounts which are higher than regulated. It can come to contamination by metal particles during its mincing in the mill, by irregular keeping and storage, and as one of the main sources of contamination is the air in the industrial zones. Plants assimilate undesired metals from the soil, and in certain conditions through leaves. These elements are accumulated largely in the root area than in organs above earth. That is the reason why the knowledge of mechanisms of accumulation, distribution and metabolism of heavy metals in plants is of high ecological, scientific and practical significance. Especially because heavy metals are among toxic matters which pollute the environment. This is the reason why wheat is selected for the analysis of the influence of heavy metals on plant culture in this paper. Wheat has dominant role in world's diet, characteristic of strategic product and it covers significant part (almost one third) of total agricultural area of plants culture planted.
Keywords: wheat; heavy metals; atomic absorption spectrophotometry(AAS); soil